DADA in Japan : Japanische Avantgarde 1920-1970 : Eine Fotodokumentation. - Kunstmuseum Düsseldorf (Düsseldorf : Kunstmuseum Düsseldorf, 1983)
Kitada, Reiichiro ; Higashiyama, Kaji ; Fujinami, Chigen ; Hamada, Hiroyasu ; Moriguchi, Hirokazu ; Ibara, Yasuo ; Sada, Shinkichi ; Nanbata, Tatsuki ; Tanaka, Kenzo ; Nishida, Shinichi ; Suga, Shigeo ; Hagi, Shun ; Suzuki, Masaki ; Ikemizu, Keiichi ; Kawaguchi, Tatsuo ; Iwakura, Shoji ; Fukumori, Kinichi ; Hisamori, Shun ; etc.
DADA in Japan : Japanische Avantgarde 1920-1970 : Eine Fotodokumentation, Kunstmuseum Düsseldorf, 18.Mai bis 26. Juni 1983
boek
Keywords: Japan